Subject: Functions
Question: - f(1)>f(0)
- f(2)>f(-3)
- f(2)=f(-2)
- f(-1)=f(3).
That is the question and if you could teach me how you do it, that would be nice because Finals are coming up next week Hi Tori, At times it is helpful to think of a fuction as a procedure that describes what to do with the input variable. For your function f the input variable is x and the procedure description,
f(x) = x ^{2} - 3 = 1 - 3 = -2. Likewise f(0) = 0^{2} - 3 = 0 - 3 = -3. Since -2 is larger than -3 statement 1 is true.
Now find f(x) for the remaining values of x, for example f(-2) = (-2)
Cheers, |